Respuesta :
Hi!
[1] -3x-7y=8
[2] 3x-2y=-44
lets take [1]
-3x-7y=8
-7y=8+3x
-7y-8=3x
3x=-7y-8
No use 3x=-7y-8 and put it in 3x-2y=-44
-7y-8-2y=-44
-9y-8=-44
-9y=-36
9y=36
y=4
then use y in 3x-2y=-44
3x-2(4)=-44
3x-8=-44
3x=-36
x=-12
Therefore, y = 4 and x = -12
[1] -3x-7y=8
[2] 3x-2y=-44
lets take [1]
-3x-7y=8
-7y=8+3x
-7y-8=3x
3x=-7y-8
No use 3x=-7y-8 and put it in 3x-2y=-44
-7y-8-2y=-44
-9y-8=-44
-9y=-36
9y=36
y=4
then use y in 3x-2y=-44
3x-2(4)=-44
3x-8=-44
3x=-36
x=-12
Therefore, y = 4 and x = -12